2005
DOI: 10.1007/s00265-005-0964-0
|View full text |Cite
|
Sign up to set email alerts
|

Dual mechanism of queen influence over sex ratio in the ant Pheidole pallidula

Abstract: Social Hymenoptera are general models for the study of parent-offspring conflict over sex ratio, because queens and workers frequently have different reproductive optima. The ant Pheidole pallidula shows a split distribution of sex ratios with most of the colonies producing reproductives of a single sex. Sex ratio specialization is tightly associated with the breeding system, with single-queen (monogynous) colonies producing malebiased brood and multiple-queen (polygynous) colonies female-biased brood. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
0
35
1
Order By: Relevance
“…colonies should specialize in male production-a split sex-ratio pattern observed in the ant Pheidole pallidula (Fournier et al 2003;de Menten et al 2005; figure 2e). …”
Section: Patterns Of Split Sex Ratio In Ants (A) Queen Control In Higmentioning
confidence: 98%
“…colonies should specialize in male production-a split sex-ratio pattern observed in the ant Pheidole pallidula (Fournier et al 2003;de Menten et al 2005; figure 2e). …”
Section: Patterns Of Split Sex Ratio In Ants (A) Queen Control In Higmentioning
confidence: 98%
“…In early spring, queens of this species increase their production of potentially reproductive offspring by laying eggs that are larger, contain more RNA, have larger polar plasms and have nurse cells with larger nuclei (Wilson 1971;Wheeler 1986). Furthermore, it is known for the ant Pheidole pallidula that queens seal offspring outcome hormonally in the egg, in part, with additions of juvenile hormones, such that individuals hatch as either potential queens or workers (De Menten et al 2005). Finally, in a recent experimental study on Pogonomyrmex harvester ants, Schwander et al (2008) showed that eggs that give rise to queens have lower levels of the hormone ecdysterone (moulting hormone).…”
Section: Predictions and Evidence For Maternal Effectsmentioning
confidence: 99%
“…The queen may directly affect larval physiology, or she may inhibit gyne production indirectly by modifying worker behavior. Hence, apart from a few notable cases of maternal effect (de Menten et al 2005) or genetic control (Julian et al 2002;Volny and Gordon 2002), the differentiation between gynes and workers seems to occur at the larval stage and depend on the type of care provided by the nurses (Wilson 1971;Brian 1973;Vargo and Passera 1991;Wheeler 1994). In addition, while workers of many species have retained functional ovaries and could increase the colony reproductive allocation by laying their own male eggs, other constraints (worker-worker conflicts over male parentage and colony-level selection) generally prevent them from doing so under queenright (QR) conditions (Woyciechowski and Łomnicki 1987;Ratnieks 1988;Hammond and Keller 2004).…”
mentioning
confidence: 99%